Astrocyte‐restricted disruption of connexin‐43 impairs neuronal plasticity in mouse barrel cortex. (21st October 2013) - Han, Yong; Yu, Han‐xiao; Sun, Man‐li; Wang, Yiner; Xi, Wang; Yu, Yan‐qin
Abstract There is intensive gap‐junctional coupling between glial processes, but their significance in sensory functions remains unknown. Connexin‐43 (Cx43), a major component of astrocytic gap‐junction channels, is abundantly expressed in astrocytes. To investigate the role of Cx43‐mediated gap junctions between astrocytes in sensory functions, we generated Cx43 knockout (KO) mice with a mouse line carrying loxP sites flanking exon 2 of the Cx43 gene and the transgenic line expressing Cre recombinase under control of the glial fibrillary acidic protein promoter, which exhibited a significant loss of Cx43 in astrocytes in the barrel cortex. Although Cx43 expression between the astrocytes measured by immunohistochemistry was virtually abolished in Cx43 KO mice, they had normal architecture in the barrel cortex but the intensity of cytochrome oxide histochemistry decreased significantly. In vivo electrophysiological analysis revealed that the long‐term potentiation of the vibrissal evoked responses in the barrel cortex evoked by high‐frequency rhythmic vibrissal stimuli (100 Hz, 1 s) was abolished in Cx43 KO mice. Current source density analysis also revealed that astrocytic Cx43 was important to the flow of excitation within the laminar connections in barrel cortex. Behavioral tests showed that the ability of Cx43 KO mice to sense the environment with their whiskers decreased. Even so, the jump‐stand experiment showed that they could still discriminate rough from smooth surfaces. Our findings suggest that Cx43‐mediated gap‐junctional coupling between astrocytes is important in the neuron–glia interactions required for whisker‐related sensory functions and plasticity.